POSYANDU STUNTING DI PUSKESMAS NGAGEL REJO: SEBUAH STUDI EVALUASI PROGRAM DI DALAM PENGURANGAN ANGKA PREVALENSI STUNTING - Permatasari, Rachmadita Evi; Oktariyanda, Trenda Aktiva (Universitas Negeri Surabaya, 2024)
Stunting is a chronic nutritional problem caused by a lack of nutritional intake, especially during the first 1000 days when a baby is born, resulting in impaired growth in children. Many toddlers in Ngagel Village tend to lose weight, this is due to congenital diseases and lack of nutrition in toddlers. This condition is thought to be due to the low economic condition of the parents of toddlers due to the current economic uncertainty. Based on the problems and conditions experienced in the Wonokromo area, the Ngagel Rejo Community Health Center created an innovation which became a superior program, namely: Posyandu Stunting with the aim of reducing the prevalence rate of stunting in Ngagel Village. This type of research is qualitative research with a descriptive analytical approach that refers to the program evaluation model. The analysis technique used uses content analysis and discourse analysis. Data collection was carried out using observation, interviews and documentation techniques. The research findings show that (1) the Ngagel Rejo Community Health Center does not have a long-term plan related to Posyandu Stunting that has been formulated, (2) the Ngagel Rejo Community Health Center has carried out all activities related to efforts to reduce stunting in toddlers in Ngagel Village, (3) There are differences in toddler data stunting from the Ngagel Rejo Community Health Center and the Surabaya City Health Service. The author's recommendations that can be used as input from the results of this research are (1) To achieve zero growth stunting, the Ngagel Rejo Health Center needs a long-term plan related to Stunting Posyandu, (2) So that there are no differences in data from the Ngagel Rejo Health Center and the Health Service, it is important to provide an application or website that contains accurate stunting data.